A number theory problem by Alejandro Castillo

1 m + 1 n 1 m n 2 = 3 4 \large \dfrac1m + \dfrac1n - \dfrac1{mn^2} = \dfrac34

Let all the solutions of the pairs of integers ( m , n ) (m,n) that satisfy the equation above be denoted by ( m 1 , n 1 ) , ( m 2 , n 2 ) , , ( m k , n k ) (m_1, n_1), (m_2, n_2), \ldots, (m_k, n_k ) . Find i = 1 k ( m i + n i ) \displaystyle \sum_{i=1}^k (m_i + n_i) .


The answer is 5.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

4 solutions

Akash Shukla
Jul 13, 2016

1 m + 1 n 1 m n 2 = 3 4 \dfrac{1}{m}+\dfrac{1}{n}-\dfrac{1}{mn^2} = \dfrac{3}{4}

( m + n ) n 1 m n 2 = 3 4 \dfrac{(m+n)*n-1}{mn^2}=\dfrac{3}{4}

4 m n + 4 n 2 4 = 3 m n 2 4mn+4n^2-4=3mn^2

4 ( m n 1 ) = n 2 ( 3 m 4 ) 4(mn-1)=n^2(3m-4)

n 2 = 2 2 m n 1 3 m 4 n^2=2^2\dfrac{mn-1}{3m-4}

Here m n 1 3 m 4 \dfrac{mn-1}{3m-4} must be a perfect square.

Here if m m is even, then denominator is always even and numerator is always odd.

Proof, m = 2 k m=2k \implies m n 1 3 m 4 = 2 k n 1 3 ( 2 k ) 4 \dfrac{mn-1}{3m-4}= \dfrac{2kn-1}{3(2k)-4} , As 2 k n 2kn is always even so 2 k n 1 2kn-1 is always odd.

While, 3 m 4 = 3 ( 2 k ) 4 = 2 ( 3 k 2 ) 3m-4=3(2k)-4=2(3k-2) is always even. So this cannot be possible.

Hence m m must be odd.For m = 3 m=3 we get n = 2 n=2 Now for higher values of m m , the value of n 2 n^2 will be in fraction. So it is not possible.

Hence, m + n = 3 + 2 = 5 m+n = 3+2=\boxed{5}

Sasha Chabanov
Jul 16, 2016

1 m + 1 n 1 m n 2 = 3 4 \dfrac{1}{m} + \dfrac{1}{n} - \dfrac{1}{mn^2} = \dfrac{3}{4}

Clearly, m , n 0 m,n \neq 0 .

Rearranging the condition, we get: ( 3 m 4 ) n 2 ( 4 m ) n + 4 = 0 (3m - 4)n^2 - (4m)n + 4 = 0 .

Solving yields: n = 2 m ± m 2 3 m + 4 3 m 4 n = 2*\dfrac{m \pm \sqrt{m^2 - 3m + 4}}{3m - 4} .

Therefore, m 2 3 m + 4 m^2 - 3m + 4 has to be a perfect square.

Let us consider an equation:

m 2 3 m + 4 = k 2 , m^2 - 3m + 4 = k^2, where k k is integer.

Calculating the discriminant, we get:

D = 9 ( 4 k 2 ) = 5 + k 2 D = 9 - (4 - k^2) = 5 + k^2 , which has to be a perfect square as well, and it can only be true if k = 2 k = 2 .

In this case m = 0 m = 0 and m = 3 m = 3 are both solutions, but m 0 m \neq 0 by condition. So, m = 3 m = 3 .

Finding n n yields n = 2 n = 2 and the only pair of integers we get is ( m , n ) = ( 3 , 2 ) (m, n) = (3, 2) .

So, the answer is m + n = 3 + 2 = 5 m + n = 3 + 2 = \boxed{5}

Sal Gard
Jul 14, 2016

Consider the equation 1/m+1/n-1/mn^2=3/4. This can be simplified using 1/m+1/n=(m+n)/mn because one can multiply 1/m by n/n and vice versa to keep equality. Now n(m+n)/(mn^2)-1/(mn^2)=3/4. This rearranges to n(m+n)-1=3(mn^2)/4. Nw we have 4(nm+n^2-1)=3(mn^2). This rearranges to 4nm+n^2-3mn^2=4. Now factor out the n. Since we are restricted to integer domain, n must be a positive or negative factor of 4. Trying out values leads to the sole solution (m,n)=(3,2) and the answer is 5.

Oscar Donlan
Aug 2, 2016

Note that, 1 m + 1 n 1 m n 2 = 3 4 \frac{1}{m}+\frac{1}{n}-\frac{1}{mn^2} = \frac{3}{4} would imply: ( 9 m n 12 n 16 ) ( 3 n 4 ) = 28 (9mn-12n-16)(3n-4)=28 (after some re-arranging) .Hence, ( 3 n 4 ) (3n-4) | 28 28 and considering 3 n 4 2 3n-4 \equiv 2 m o d ( 3 ) mod(3) , it must be the case that ( 3 n 4 ) (3n-4) is a factor of 28 which is congruent to 2 2 modulo 3.

That is, ( 3 n 4 ) { 1 , 2 , 7 , 14 , 28 } (3n-4) \in \{-1,2,-7,14,-28\}

Setting 3 n 4 3n-4 equal to each of these in turn and then equating 9 m n 12 n 16 9mn-12n-16 to the complementary divisor yields a value for m m . In only one case the value of m is a non-zero integer and hence the only solution is m = 3 , n = 2 m=3 , n=2 (calculation shows that this is indeed a solution to the original equation).

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...